A look to the relationship between wellness-sicicness and work process - Arbeláez, Martha C.; Uribe-S., Carlos Mario (Revista Facultad de Odontología Universidad de Antioquia, 2018)
The following- paper presents a view of the wellness-sickness concept and its relationship with the production process, it revised the .histarical mornents who have reduced differents point of views to the medica'practice applied to publi c health. It is of interest the thearical support from the social medicine school, that allows an aproach to health in a coherent áshion,basedupon theories from social ciences, all fonns o fInguages and realizy. Previous published incompletecausative models sode as: unicausaliT, multicausalio and ecologicaltriade,allow us tobuild upa social thery morder tounderstand the human sick-wellness process. Antropology desaibe cultural causativemodels to interpret diseases and suggeststrategies tochanges in lile condocts and szyles that allow zis to adoptpreventive measures in fiont afsuchcausalizy. It also shows tha t work is not a process parallel to Tríe, itis anstructural part of it. Since the appearence of the 100 la w, health is concibed asa service, asa right of all citicens to look for care in an HPI. Such kind of institutions belong to the market system and ruledbylaws of: affer, demand and to over come the functionalist approach, the work of the social scientists willbecame fundamental in the interdisaplinazy research team.